Evaluating the advancements in a recently introduced universal adhesive compared to its predecessor - Arefin Alam; Monica Yamauti; Abu Faem Mohammad Almas Chowdhury; Xiaohong Wang; Pedro Álvarez-Lloret; Enrique-Ezra; Carolina Cifuentes-Jiménez; Rupak Dua; Masahiro Iijima; Hidehiko Sano (Elsevier, 2024)
Background/purpose: The dental adhesive market is constantly evolving to meet the demands of dentists and patients, but new products and upgrades should be rigorously evaluated before being used in clinical practice. This study investigated the physicomechanical properties and dentin bonding efficacy of a newly upgraded universal adhesive compared to its predecessor. Materials and methods: Twenty-four molars were divided into four groups (n = 6/group) based on adhesive (new vs. predecessor) and application mode [self-etch (SE) vs. etch-and-rinse (ER)] for evaluating their dentin microtensile bond strength (μTBS), failure pattern, and bonding interface. Additional thirty-six molars' crowns were perpendicularly sectioned to obtain flat mid-coronal dentin discs. The opposing dentin surfaces of each disc received contrasting treatments (new/predecessor adhesive applied in SE/ER mode), resulting in six interventions. The bonded discs (n = 6/intervention) were used to assess the adhesives' survival probability employing a double-sided μTBS test. The other physicomechanical properties examined were adhesives' oxygen inhibition layer (OIL), viscosity, hardness, elastic modulus, degree of conversion (DC), and in-situ DC. Results: Both adhesive versions showed similar μTBS (P > 0.05), failure pattern (P > 0.05), and survival probability (P > 0.008). ER mode promoted resin tag formation and exhibited a slender adhesive layer for both adhesives. The newer adhesive version showed a thinner adhesive layer in general with narrower OIL (P < 0.001), less viscosity (P < 0.001), higher hardness (P < 0.05), elastic modulus (P < 0.05), DC (P < 0.001), and in-situ DC (P < 0.001). Conclusion: While the newly updated adhesive had superior physicomechanical properties with more fluidity, its dentin bonding efficacy and survival probability were comparable to its predecessor.